Strategi Pabligbagan Pasikian Yowana Bali Pada Programa 4 Radio Republik Indonesia (RRI) Denpasar - Paramitha, Komang Ayu Tri Paramitha; I Dewa Ayu Hendrawathy Putri; I Gusti Ngurah Pertu Agung (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The Republic of Indonesia Radio Public Broadcasting Institute (LPP RRI) Denpasar is one of Programa 4 which discusses the cultural segment and has the function of preserving Balinese culture. Therefore, it is necessary to raise the Communication Strategy of Pabligbagan Pasikian Yowana Bali at Programa 4 RRI Denpasar. To find out the Communication Strategy of Pabligbagan Pasikian Yowana Bali in Programa 4 RRI Denpasar, research was conducted regarding the Communication Strategy Model of Pabligbagan Pasikian Yowana Bali in Programa 4 RRI Denpasar, Barriers to Pabligbagan Pasikian Yowana Bali Communication Strategy in Programa 4 RRI Denpasar and the Implications of Communication Strategy of Pabligbagan Pasikian Yowana Bali at Program 4 RRI Denpasar. The methodology of this study uses a qualitative approach with descriptive analysis which aims to obtain an overview of the problem and determine the work steps in this study regarding the Communication Strategy of Pabligbagan Pasikian Yowana Bali in Program 4 Radio Republik Indonesia (RRI) Denpasar in the Literacy of the Young Generation in the Era of the Industrial Revolution Society 5.0. Therefore, it is necessary to use the right methods to help the smooth running of research.The theory used to dissect this research problem is the Five Step Communication Planning Model, namely Research, Planning, Implementation, Evaluation or Measurement and Reporting, Rhetoric Theory and Dependency Theory of Mass Communication Effects.